The Relationship Between Diet And The Risk Of Hypertension In Biology Education Students Of Samudra University - Mardiah; Akbar, M. Ali; Zunita, Nia; Nisa, Khairun; Zahara, Arini Shinta; Pepayosa, Enca (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
Diet is the most important behavior that can influence nutritional conditions. This can happen because the health level of a person and society can be influenced by the food and drink consumed based on its quality and quantity. Eating patterns that can cause hypertension are unhealthy foods such as snack habits, snack habits, instant food and fast food or foods that contain potassium. Foods that contain excessive fat can pose a risk of hypertension because they increase cholesterol levels in the blood. This study aims to determine the relationship between diet and the risk of hypertension among students, especially biology students at Ocean University. This research uses quantitative descriptive methods, using a quantitative approach using analytical observational research. The data analysis technique used in this research is two analyses, namely univariate analysis and bivariate analysis. The results of this study showed that there were 10 people with a percentage of 31.25% who were detected as normal (not at risk of developing hypertension) and there were 22 people with a percentage of 68.75% who were detected as having a risk of developing hypertension. This study also shows that there is a relationship between diet and the risk of hypertension with the value ∑X2 table (3.48)> ∑X2 calculated (2.6). So you need to pay attention to your diet to avoid the risk of hypertension. Keywords: Hypertension, Dietary Habit, Student